Students’ Self-Directed Learning at Language University - Yakovleva, Anastasia Nikolaevna (2020)
The article is devoted to the problem of self-directed learning of students of Language University. Self-organization is an integral characteristic of personality development. The authors studied the components of self-organization: self-assessment, some personal qualities, etc. Some peculiarities of self-organization of Language University students were revealed with the standardized questionnaires and questionnaires based on self-assessment. It turned out that students with high cognitive capacity have insufficient level of self-organization, low cognitive activity. Self-organization is formed in the process of independent work and autonomous learning. The authors consider the problem of educational autonomy development of students while learning foreign languages as an interdisciplinary problem, as a subject area of linguopedagogics. The research also studied methodological strategies for learning new vocabulary. The development of learning style activity depends on certain personal qualities related to native traits. The research about self-directed leaning of students is the basis for the development of pedagogical activities with the aim of developing the optimal style of educational methods. The content of this research is both theoretical and practical; we are creating conditions for effective cognitive activity.